2017
DOI: 10.1080/01480545.2016.1278227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of T-2 toxin-injected shrimp muscle extracts on mouse macrophage cells (RAW264.7)

Abstract: Following intramuscular injections of 0.1 mL, 3 mg kgBW(1/10 LD) T-2 toxin (T-2), the tissue concentration of T-2 in shrimp was quantitatively detected using LC-MS/MS. The biological half-time (t) of T-2 in blood was 40.47 ± 0.24 min. The highest number of intramuscular T-2 shrimp could tolerate when given at blood t intervals was 4. The shrimps which were injected 5 T-2 died. The T-2 toxin highest accumulation was 0.471 ± 0.012 ng gBW. The effect of toxic shrimp muscle subjected to different processing condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…A wealth of research papers clearly indicate a negative influence of T-2 toxin on the hematocytes, hepatocytes, chondrocytes, intestinal function, immune system, and reproductive system (Adhikari et al, 2017; He et al, 2012; Huang et al, 2018; Leal et al, 1998; Moosavi et al, 2016; Wu et al, 2017; Yang et al, 2010; Zhang et al, 2018). Our research team has also reported the negative effects of T-2 toxin on male fertility and other reproductive pathologies in male animals (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of research papers clearly indicate a negative influence of T-2 toxin on the hematocytes, hepatocytes, chondrocytes, intestinal function, immune system, and reproductive system (Adhikari et al, 2017; He et al, 2012; Huang et al, 2018; Leal et al, 1998; Moosavi et al, 2016; Wu et al, 2017; Yang et al, 2010; Zhang et al, 2018). Our research team has also reported the negative effects of T-2 toxin on male fertility and other reproductive pathologies in male animals (Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Contamination of feed ingredients with toxic concentrations of mycotoxins has been so serious in recent years, that it seems likely to limit the expansion of aquaculture in Asia 28,29 . It has been shown that dietary aflatoxin B 1 caused poor growth performance and deformities of juvenile grass carp 30 .…”
Section: Discussionmentioning
confidence: 99%
“…T-2 toxin, a fungal secondary metabolite, has immunotoxic, hepatotoxic, hematotoxic, and genotoxic properties (Adhikari et al, 2017; Huang et al, 2018; Wu et al, 2017; Yang et al, 2010; Zhang et al, 2018). T-2 toxin has been shown to induce apoptosis in lymphocytes (Shinozuka et al, 1997), thymocytes (Islam et al, 1998), rat ovarian granulosa cells (Wu et al, 2013), human chondrocytes (Liu et al, 2014), human neuroblastoma cells (Agrawal et al, 2015), and mouse Leydig cells (Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%